The diverse methods of bleomycin delivery in cutaneous warts: A literature review. Issue 1 (21st October 2020) - Kaul, Subuhi; Kaur, Ishmeet; Jakhar, Deepak; Edigin, Ehizogie; Caldito, Elena Gonzalez
Abstract: Bleomycin is a useful treatment option for recalcitrant verrucae. Several different methods of bleomycin delivery have been described, including intralesional injection, intralesional injection combined with laser, microneedling, multiple puncture and adhesive tape. We reviewed the literature to evaluate the various methods of bleomycin administration to treat warts, including the different doses, instruments and procedures used. Intralesional injection (cure rate ranged from 67.8% to 99.23%) and topical bleomycin with multipuncture or microneedling methods (63.6% to 100%) were found to be effective in the treatment of warts. Overall, pain is significantly less with microneedling and multipuncture techniques compared with intralesional injection. Bleomycin injection combined with pulsed dye laser, electroporation, or by other methods, such as, microneedle patches or adhesive tape do not seem to be more beneficial than bleomycin administered by intralesional injection, multipuncture or microneedling techniques.